(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
Although being a slow growing tumor, spinal meningiomas are often diagnosed late and presents with features of significant cord compression that essentially warrants surgical management. To assess the clinical and functional outcome of excision of dorsal spinal meningioma. Within the period of July 2003 to June 2012, retrospective review of the records of 23 patients (Male:07, Female:26, age range, 34-68 years) with postoperative histological confirmation of meningioma were evaluated. Pre- and postoperative neurological state was classified according to the Frankel scale and functional outcome was assessed according to Levy Score. Chi-squared test and z-test was used for statistical analysis using SPSS. The mean age was 48.30=03.50 years with significant female predominance. The posterior and posterolateral position was significant causing significant neuro-deficit. Satisfactory surgical results were achieved in 78.90% cases (Levy Score) and 82.82% cases (Frankel grading). Surgical resection of spinal meningiomas is a safe and effective procedure even with severe neurological deficits. JCMCTA 2013 ; 24 (2): 14-18